Identification of Klebsiella Pneumonia Isolates from Sewage Water of Some Hospitals in Wasit Province - Al-Rekaabi, Aseel Razak; Al-Deresawi, Mahdi Saber (American Journal of Biodiversity, 2025)
The specific objective of the study was to validate the identification of Klebsiella pneumoniae isolates and to identify the presence of two virulence-associated genes namely mrkD and rmpA using Polymerase Chain Reaction (PCR) method. Thirty (30) K. pneumoniae were isolated and recovered in March and April 2024 by sampling sewage samples of different hospitals in the Wasit Province along with the respective metabolism feature. The identification of isolates was done with the API 20E system and the VITEK 2 automated platform. The disk diffusion method of antimicrobial susceptibility testing was performed on 12 different antibiotics. The strongest resistant rates were with respect to Ampicillin and Amoxicillin-Clavulanic acid (100 percent), the lowest resistance was during Imipenem (5 percent). Through the PCR analysis, 14 isolates out of the 30 (47 percent) were positive with the mrkD gene and 10 of 30 (34 percent) with the rmpA gene. To sum up, it is evident that the prevalence of K. pneumoniae in sewage samples is extremely high in hospital settings, which demonstrates the danger of environmental contamination and once again explains why execution of effective waste water-treatment and infection-control methods, such as in healthcare institutions, is of paramount priority.